Assessing the Governance Quality in Community Forest User Groups: Insights from Makawanpur District, Nepal - Ghimire, Pramod (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
In recent years, forest governance has received significant global attention as a key component of sustainable forest management and utilization. In the context of Nepal, good governance within community forestry is recognized as a vital mechanism for promoting inclusive decision-making, equitable benefit-sharing, and poverty alleviation. This study was conducted in three Community Forest User Groups (CFUGs) in the Makawanpur district to assess the quality of forest governance. Both primary and secondary data were utilized, including a household questionnaire survey (n=244), key informant interviews, and discussions with executive committee members. The quality of forest governance was evaluated using four key criteria i.e. participation, transparency, accountability, and rule of law, along with their corresponding local indicators, assessed through simple quantitative methods. The findings revealed an average governance score of 69.38% across the CFUGs, with Ashok CF achieving the highest score (71.87%), followed by Okhe CF (70.31%) and Nawalpur-Saraswati CF (65.63%). Among the four governance elements, participation scored the highest, while transparency received the lowest rating. These results suggest that the quality of governance in community forests is moderately strong; there is still room for improvement. To enhance governance quality, greater emphasis should be placed on improving transparency, accountability, and inclusiveness in future interventions.